2016
DOI: 10.1118/1.4948690
|View full text |Cite
|
Sign up to set email alerts
|

Grating‐based x‐ray differential phase contrast imaging with twin peaks in phase‐stepping curves—phase retrieval and dewrapping

Abstract: Using the phase retrieval and dewrapping methods proposed to deal with the phenomenon of twin peaks in PSCs and phase wrapping, the performance of grating-based x-ray differential phase contrast radiography and CT can be significantly improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…13 Due to imperfections, such as nonuniform gold layer thickness, in the absorption grating induced in the fabrication process, 14 it has been reported that twin-peaks at significant different heights may exist in the PSCs. 8,15,16 In general, as noted in Ref. 17, the polychromatic X-ray spectrum is another important factor that may cause the twin-peaks phenomenon in the PSCs.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…13 Due to imperfections, such as nonuniform gold layer thickness, in the absorption grating induced in the fabrication process, 14 it has been reported that twin-peaks at significant different heights may exist in the PSCs. 8,15,16 In general, as noted in Ref. 17, the polychromatic X-ray spectrum is another important factor that may cause the twin-peaks phenomenon in the PSCs.…”
Section: Introductionmentioning
confidence: 93%
“…[1][2][3] Initially, this imaging method can only be implemented with highly brilliant synchrotron x-ray sources. 1,2 Recently, the requirement for an x-ray source with complete spatial coherence has been relaxed via the adoption of Talbot interferometry, 4 which can be implemented with a micro-focus tube [5][6][7][8] or a multi-slit source grating in front of an x-ray tube with a finite focal spot. [9][10][11] By fulfilling the requirement for partial spatial coherence, the grating based differential phase contrast CT is compatible with polychromatic x-ray sources that are readily available in practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modregger et al 23 proposed a deconvolution-based approach for information retrieval, which does not depend on the assumption of a sinusoidal phase-stepping curve. The noise properties of this algorithm were later investigated by Weber et al 24 Yang et al 25 developed a phase-stepping reconstruction method for nonideal gratings, which may exhibit a phase-stepping curve with twin peaks. The problem of estimating the position of misaligned phase steps was considered by Pelzer et al 26 and Seifert et al 27 They showed that an algorithm known in optics 28 can be used to retrieve the correct phase-stepping positions, if the Talbot-Lau interferometer is detuned by rotation of either G1 or G2, such that sufficient moiré fringes appear in the reference phase, and if a sufficient number of phase steps are available.…”
Section: Prior Workmentioning
confidence: 99%
“…Currently, the synchrotron‐based XPCI techniques, propagation phase‐contrast imaging (PPI) and X‐ray grating interferometry (XGI), have dominated the nondestructive 3D visualization of biological tissues in hard X‐ray domain. Both techniques perform well over a large energy range in imaging application without requiring a strictly monochromatic or collimated X‐ray wave and display different characteristics of intensity distribution recorded on detectors, and different physical quantity in raw data determines different phase retrieval method.…”
Section: Introductionmentioning
confidence: 99%